Metodologia y aplicacion de la propagacion rapida en yuca: Experiencias en Panama - Chavez F., M. (International Center for Tropical Agriculture, 1991)
Two cassava propagation techniques, proposed by CIAT, with small modifications according to the location and climatic conditions of the corresponding region of Panama, are described. The 1st method, using stem cuttings or sprouts, allows between 12,000 and 24,400 cuttings to be produced per yr, each one 20-25 cm long and apt for commercial planting. The 2nd method, single leaf- bud cuttings, is also being applied successfully in the country. (CIAT)